Життєвий шлях, творчий доробок та громадська діяльність С. В. Пилипенка (1891–1934 рр.) - Білас, Юлія Валеріївна (Національний технічний університет "Харківський політехнічний інститут", 2025)
Дисертаційна робота присвячена дослідженню біографії українського письменника та громадського діяча Сергія Володимировича Пилипенка, а також персоніфікації його особистого внеску у формування соціокультурного середовища першої третини ХХ століття. Зазначений період сповнений сторінками боротьби за українську самостійність як за часів імперської доби, так і після неї. Після поразки Української революції, в умовах входження українських земель до більшовицької держави, продовжувався розвиток української культури, мистецтва, науки. Актуальність тематики пояснюється необхідністю аналізу діяльності ключових особистостей української національної еліти на тлі політичних репресій 1920-х – 1930-х рр. Поступове повернення із забуття навмисно викреслених прізвищ репресованих діячів доби Розстріляного відродження, відновлення пам’яті про них, та меморіалізації їх доробку в сучасному історико-культурному просторі вимагає ретельного відтворення наукових та інтелектуальних біографій науковців, митців і громадських діячів тощо. Дослідження акцентоване на громадському доробку та особистому внеску Сергія Пилипенка у розвиток соціокультурного середовища України першої третини ХХ століття. Мета – спираючись на опрацювання історичних джерел та наукової літератури здійснити комплексне дослідження біографії і провести реконструкцію життєвого шляху українського письменника Сергія Володимировича Пилипенка. Досягнення визначеної мети передбачає вирішення поставлених конкретно-проблемних завдань: – Провести історіографічний аналіз наукової літератури для з’ясування ступеню дослідження даної проблеми, сформулювати та класифікувати джерельну базу дослідження, обґрунтувати методологічні засади дослідження; – Розкрити передумови формування особистості Сергія Пилипенка в дитячі та юнацькі роки, з’ясувати значущість навчання Сергія Пилипенка в Київському університеті для становлення його професійних навичок і громадянської позиції; – Охарактеризувати його творчий і журналістський доробок у Першій світовій війні та в добу Української революції; – Визначити напрями діяльності Сергія Пилипенка у «харківський» період життя, спрямовані на організацію літературно-мистецького середовища, конструювання нового українського радянізованого суспільства, реформування української писемності і науковий розвиток шевченкознавства протягом 1920-х рр.; – Розглянути останні роки життя і професійної діяльності письменника в умовах розгортання репресій на початку 1930-х рр., аналізуючи штучну інкримінацію, використану проти Сергія Пилипенка; – Узагальнити фактологічний матеріал про процес історичної реабілітації діяча та структурувати етапи меморіалізації його особистості. Об’єктом дослідження є соціокультурне середовище України першої третини ХХ в контексті діяльності провідних представників української національної еліти. Предмет дослідження – відтворення багатомірних напрямів діяльності українського громадського діяча і письменника Сергія Пилипенка (1891–1934 рр.) та його ролі в українському громадському, науковому й культурно-мистецькому середовищі першої третини ХХ століття. Відновлення історичної пам’яті та меморіалізація репресованого діяча в українському загальнокультурному просторі.

The dissertation is devoted to the reconstruction of a comprehensive scientific biography of the Ukrainian writer and public figure Serhiy Volodymyrovych Pylypenko, as well as the personification of his personal contribution to the formation of the Ukrainian socio-cultural environment, Ukrainian science and the cultural and artistic environment of the first third of the twentieth century. The specified period is full of pages of the struggle for Ukrainian independence both during the imperial era and after it. After the defeat of the Ukrainian Revolution, in the conditions of entry of Ukrainian lands into the Bolshevik state, the development of Ukrainian culture, art, science continued. The relevance of the topic is explained by the need to analyze the activities of key figures of the Ukrainian national elite against the backdrop of political repressions of the 1920s – 1930s. The gradual revival of the deliberately erased names of repressed figures of the era of the “Shooted Renaissance”, the restoration of memory about them, and the memorialization of their achievements in the modern historical and cultural space requires the full reproduction of scientific and intellectual biographies of scientists, artists, and public figures, etc. The study focuses on the public achievements and personal contribution of Serhiy Pylypenko to the development of the socio-cultural environment of Ukraine in the first third of the twentieth century. The purpose of the study is to carry out a systematic study of the scientific biography and reconstruct the life path of the Ukrainian writer Serhiy Volodymyrovych Pylypenko, based on a comprehensive study of historical sources and scientific literature. Achieving a certain goal involves the solution of specific problems set: – To carry out a historiographical analysis of scientific literature to find out the degree of research of this problem, to formulate and classify the source base of the study, to substantiate the methodological foundations of the study; – To reveal the prerequisites for the formation of Sergey Pylypenko's personality in childhood and adolescence, to find out the importance of Sergei Pylypenko's training at Kyiv University to develop his professional skills and civic position; – To characterize his creative and journalistic work in the First World War and in the Ukrainian Revolution; – To determine the directions of activity of Sergey Pylypenko in the "Kharkiv" period of life aimed at organizing a literary and artistic environment, constructing a new Ukrainian sovietized society, reforming Ukrainian writing and scientific development of Shevchenko studies during the 1920s; – To consider the last years of the life and professional activity of the writer in the conditions of deployment of repression in the early 1930's, analyzing the artificial incrimination used against Sergei Pylypenko; – To summarize the factual material about the process of historical rehabilitation of the figure and to structure the stages of memorialization of his personality. The object of the study is the socio-cultural environment of Ukraine of the first third of the 20th in the context of the leading representatives of the Ukrainian national elite. The subject of the study is the reproduction of the multidimensional directions of activity of the Ukrainian public figure and writer Serhiy Pylypenko (1891–1934) and his role in the Ukrainian public, scientific and cultural and artistic environment of the first third of the 20th century. Restoration of historical memory and memorialization of the repressed figure in the Ukrainian general cultural space. The introduction substantiates the relevance of the need for a comprehensive study of the biography of Serhiy Pylypenko, outlines the object, subject, chronological and territorial boundaries of the study. The purpose of the scientific research is determined, as well as the tasks determined by the specified purpose. The methodological basis of the dissertation work is characterized. The scientific novelty is presented and information is provided on the connection of the work with scientific programs, plans and topics. The practical significance of the results obtained is highlighted, information is provided on the personal contribution of the applicant and a list of publications on the topic of the dissertation is presented.
Life path, creative achievements and public activities of S. V. Pylypenko (1891–1934)
Keywords: Сергій Пилипенко; національна ідентичність; культура; громадська діяльність; культурна спадщина; усна історія; пам'ять; Харків; біографія; генеалогічне дослідження; Спілка селянських письменників «Плуг»; Слобожанщина; політичні репресії; музей; краєзнавство; Serhiy Pylypenko; national identity; culture; public activity; cultural heritage; оral history; memory; Kharkiv; biography; genealogical research; Union of Peasant Writers "Plough"; Slobozhanshchyna; political repressions; museum; local history